Role of residual stress on phase transformations of Pb(Zr0.50Ti0.50)O3 thin films obtained from chemical route - Lima, E. C.; Araujo, E. B. [UNESP] (Taylor & Francis, 2016)
abstract: The effects of heat treatment on the phase transformations of lead zirconate titanate Pb(Zr0.50Ti0.50)O3 (PZT) thin films were studied. The pyrolysis temperature directly affected the densification, residual stresses, and suppression of the pyrochlore phase observed in the studied films. The evolution of the crystalline phases and the residual stress were characterized by different temperatures of pyrolysis in PZT thin films, using the X-ray diffraction technique. The phase transformations in the films are discussed in terms of theoretical and experimental calculations of residual stress.
Keywords: phase transformation; PZT thin films; residual stress